Recent Advances in the Synthesis of Unsymmetrical Bisindolylmethane Derivatives - Palmieri, Alessandro; Petrini, Marino (Synthesis, 2019)
This review article summarizes the fundamental synthetic procedures aimed at the preparation of unsymmetrical bisindolylmethanes that have appeared in the literature since 2010. To this goal, reactive electrophilic indole-containing intermediates are mostly generated from indolylmethanols, indolylmethanamines, and indolylmethanthio derivatives and then made to react with simple or functionalized indoles. The asymmetric synthesis of bisindolylmethanes can be also achieved under chiral-catalyzed conditions.1 Introduction2 Direct Three-Component Coupling3 Reaction of Indolylmethanols4 Reaction of Indolylmethanamine Derivatives5 Reaction of 3-Vinylindoles6 Reaction of indolylmethanthio Derivatives7 Bisindolylmethanes by Ring Closure of Alkyne Derivatives8 Miscellaneous Methods9 Conclusion
Keywords: asymmetric synthesis; bisindolylmethanes; chiral catalysis; electrophilic substitution; indoles